Prescribing Errors With Direct Oral Anticoagulants and Their Impact on the Risk of Bleeding in Patients With Atrial Fibrillation. (November 2021) - Raccah, Bruria Hirsh; Erlichman, Yevgeni; Pollak, Arthur; Matok, Ilan; Muszkat, Mordechai
Introduction: Anticoagulants are associated with significant harm when used in error, but there are limited data on potential harm of inappropriate treatment with direct oral anticoagulants (DOACs). We conducted a matched case-control study among atrial fibrillation (AF) patients admitting the hospital with a chronic treatment with DOACs, in order to assess factors associated with the risk of major bleeding. Methods: Patient data were documented using hospital's computerized provider order entry system. Patients identified with major bleeding were defined as cases and were matched with controls based on the duration of treatment with DOACs and number of chronic medications. Appropriateness of prescribing was assessed based on the relevant clinical guidelines. Conditional logistic regression was used to evaluate the potential impact of safety-relevant prescribing errors with DOACs on major bleeding. Results: A total number of 509 eligible admissions were detected during the study period, including 64 cases of major bleeding and 445 controls. The prevalence of prescribing errors with DOACs was 33%. Most prevalent prescribing errors with DOACs were "drug dose too low" (16%) and "non-recommended combination of drugs" (11%). Safety-relevant prescribing errors with DOACs were associated with major bleeding [adjusted odds ratio (aOR) 2.17, 95% confidence interval (CI) 1.14-4.12]. Conclusion: Prescribers should be aware of the potential negative impact of prescribing errors with DOACs and understand the importance of proper prescribing and regular follow-up.